The Role of Industry Players’ Understanding and Concern in Green Accounting Implementation and Business Sustainability: Evidence from Pempek MSMEs in Palembang - Nur Fitri Dewi; Alfi Maghfuriyah (Neo Journal of economy and social humanities, 2026)
Industry players’ understanding and concern play a crucial role in shaping the implementation of green accounting and its implications for business sustainability among pempek MSMEs in Palembang City. Employing a quantitative approach, the data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The findings reveal that industry players’ understanding and concern have a significant positive effect on green accounting implementation. Furthermore, green accounting implementation exerts a significant positive influence on business sustainability. In contrast, understanding and concern do not directly affect business sustainability. Mediation analysis further confirms that green accounting implementation fully mediates the relationship between industry players’ understanding and concern and business sustainability. These results indicate that awareness and concern alone are insufficient to enhance sustainability performance unless they are translated into concrete green accounting practices. Within the context of pempek MSMEs, green accounting emerges as a key mechanism that converts environmental awareness into sustainable business outcomes. This research enriches the literature on green accounting and MSME sustainability while offering practical insights for policymakers and pempek MSME development initiatives in Palembang City.